Comparative Autonomic Responses to Diagnostic Interviewing between Individuals with GAD, MDD, SAD and Healthy Controls - Diamond, Allison E.; Fisher, Aaron J. (Frontiers in Human Neuroscience, 2017)
Dysregulation of the autonomic nervous system (ANS) has been well documented in individuals diagnosed with a range of psychological disorders. Moreover, these disorders both confer an increased risk of cardiovascular disease – which may relate to increased sympathetic and decreased parasympathetic tone. Extant research has indicated a reduction in autonomic flexibility in GAD, and while reduced flexibility has also been seen in MDD, the specific physiological alterations have been more difficult to categorize due to methodological limitations. Prior studies have largely assessed autonomic functioning in stress paradigms or at the trait level, yet to date no research has investigated the ANS during a diagnostic interview. In this study we sought to identify physiological differences in both branches of the ANS across diagnostic categories in the context of a diagnostic interview. Participants (n=82) were administered a structured clinical interview, during which heart rate (HR), respiratory sinus arrhythmia (RSA), and pre-ejection period (PEP) were recorded in participants carrying a diagnosis of GAD (n=34), MDD (n=22), Social Anxiety Disorder (SAD; n=15), and healthy controls (n=27). Person-specific linear regression models were employed to assess the level and slope for HR, RSA, and PEP throughout the course of the interview. A multivariate analysis of variance model was conducted to baseline differences in HR, RSA, and PEP between diagnostic groups. Multiple regression models were then conducted to differences in slope of HR, RSA, and PEP throughout the course of the interview amongst diagnostic groups, including both suppression and worry as moderators. Results indicated significant increases in RSA throughout the interview in MDD (p = 0.01) compared to healthy controls. Worry itself was found to be a more significant predictor of both decreased PEP (p = 0.02) and increased HR (p = 0.05). Suppression exhibited a dampening effect on individuals with worry and GAD, whereby those who suppressed had dampened HR responsiveness compared to those who did not suppress. These findings are consistent with existing literature supporting a decreased autonomic flexibility in certain psychological disorders, as well as indicate distinct physiological differences across certain transdiagnostic features of mood and anxiety disorders.